Social Concerns of Kautilya and Laws on Wage and Consumer Rights - Harekrushna Mishra (SIASAT, 2022)
Arthasastra is a Sanskrit text that deals with the Indian Polity and Hindu Social Laws. There are hundreds of laws made by this tradition which are also relevant even to these days. The Kautilya Arthasastra – written at the turn of the 5th to the 3rd century BC – is a classical work of political theory and International relations theory as well. The Arthasastra is a theoretical and normative work that features six pivotal idea clusters 1) State power, 2) Raison defeat, 3) Correlation of forces, 4) The Saptanga theory, 5) The Sadgunya theory, 6) The Matsya-nyaya theory, etc. The Kautilya Arthasastra also acts as the key to understanding the politicostrategic culture of modern India. Here this research shall focus on the ideas of Arthasastra on the social concern of Kautilian Laws with special reference to wage and consumer’s rights and mostly on the punishments for breach of contract and fraud.